Postpartum continuous epidural analgesia on pain, sleep quality, and emotional state in childbearing women: a randomized controlled trial - Zhang, Jialei; Li, Jing; Zhang, Xiaoling; Wu, Jie (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the effects of continuous epidural analgesia on postpartum pain and sleep quality in postpartum women.MethodsFirst-time mothers who received labor analgesia in the obstetrics department of Changzhi People’s Hospital, affiliated to Changzhi Medical College, from November 2024 to December 2024, were selected and randomly divided into the control group (C group) and the experimental group (E group). The control group received epidural labor analgesia after entering the labor process, using 10 mL of 1% ropivacaine, 50 μg of sufentanil, and 90 mL of 0.9% sodium chloride injection. The initial bolus dose was 6 mL, the injection rate was 6 mL/h, with additional doses of 4 mL each time, a lockout time of 15 min, and continuous infusion until the fetus was delivered and then stopped. The experimental group received epidural labor analgesia after entering the labor process and continued the infusion for 2 days after the fetus was delivered, with the same medication concentration and infusion rate as the control group. All postpartum mothers had blood samples taken before sleep on the 1st and 3rd days after delivery to measure serum melatonin levels. The visual analog scale (VAS) was used to compare pain scores (including sitting pain, sleep pain, and urination pain) on the 1st and 3rd days after the fetus was delivered in both groups. The modified Bromage score (MBS) was used to evaluate the mobility of the lower limbs. On the 3rd postoperative day, the Edinburgh Postnatal Depression Scale (EPDS) and the Pittsburgh Sleep Quality Index (PSQI) were used to assess sleep quality and emotional state, and the occurrence of depression in both groups.ResultsThe VAS scores for sitting pain, sleep pain, and urination pain on the 1st and 3rd days after the fetus was delivered were all lower in the experimental group compared to the control group (p < 0.05). There was no significant difference in MBS between the two groups on the first day after delivery (p > 0.05), and the experimental group had higher scores than the control group on the 3rd day (p < 0.05), but this did not significantly affect the patients’ daily lives in the experimental group. In addition, the EPDS and PSQI scores were both higher in the experimental group than in the control group (p < 0.05). The levels of melatonin in the body were also significantly higher in the experimental group than the control group (p < 0.05).ConclusionThe implementation of continuous epidural analgesia after childbirth can significantly alleviate postpartum pain, improve sleep quality, and reduce the occurrence of postpartum depression without affecting the mother’s mobility.